Role of envelope compactness and glycosylation in HIV-1 resistance to neutralising antibody responses - Moyo, Thandeka (Division of Immunology, 2018)
Understanding the mechanisms used by HIV-1 to evade antibody neutralisation may contribute to the design of a high-coverage vaccine. This thesis explores the mechanism used by a Tier 3 virus leading to its high antibody neutralisation resistance phenotype. This thesis also describes how the glycans at the base of the V3 loop contribute to (i) breadth and potency in a cohort of unselected HIV-1-infected individuals and (ii) the selective pressures resulting from the V3/glycans shielding the virus from neutralisation and the glycans themselves being targets of broad antibody responses. HIV-1 isolates that are highly resistant to broadly neutralising antibodies could limit the efficacy of an antibody-based vaccine. For this reason, it is important to understand the mechanisms behind high HIV-1 resistance to neutralising antibodies. Chapter 2 and Chapter 3 of this thesis describe virus 253-11, a highly neutralisation resistant virus, which is particularly resistant to commonly-elicited, anti-membrane proximal external region (MPER) antibodies in sera. To further understand its resistance, mutations in the MPER were introduced that are known to delay fusion following CD4-binding and thus increase the time the virus spends in the open conformation. Interestingly, we found that these mutations affect the 253-11 Envelope (Env) spike before CD4-binding by destabilising the closed trimer structure. From these data, we hypothesized that the neutralisation resistance of 253-11 was due to an unusually tight, compact pre-fusion Env trimer that resists transient changes to the open conformation. The open conformation frequently exposes narrowly-neutralising antibody epitopes. Because the unliganded 253-11 Env presumably transitions infrequently into the open conformation, it would be able to evade these responses. 253-11 was sensitive to most but not all of the most potent broadly neutralising antibodies (bnAbs) tested, most likely because those broadly neutralising antibodies can access their epitopes in the pre-fusion Env conformation. To gain further information about the structure of the 253-11 Env, we designed a recombinant 253-11 SOSIP trimer and found it to be stable and predominantly adopt a closed conformation. The crystal structure of the SOSIP trimer revealed structural elements likely responsible for 253-11 Env compactness including the inward disposition of the heptad repeat helices and gp120 protomers towards the trimer axis. Taken together, the data from Chapter 2 and Chapter 3 highlight an underappreciated Env compactness mechanism of HIV-1 resistance to neutralising antibodies and these data may be useful in HIV-1 immunogen design research. Previous candidate HIV vaccines have failed to induce wide-coverage neutralising antibodies capable of substantially protecting vaccinees. A key approach in HIV immunogen development has been to define and model epitopes recognised by anti-HIV bnAbs. Candidate immunogen models identified by bnAbs include the V3/glycans, the V2/apex and the MPER epitopes. Autoreactivity and polyreactivity of anti-V3/glycan and anti-MPER antibodies are thought to pose both direct and indirect barriers to achieving neutralisation breadth. Chapter 4 of this thesis explored which of these bnAb epitopes were associated with breadth and potency in a South African cohort of chronically HIV-infected individuals. The study found that antibodies targeting the V3/glycans were associated with breadth and potency. In contrast, antibodies to the V2/apex were not associated with neutralisation breadth/potency. This suggests that auto/polyreactivity are not critical factors in the development of breadth and potency and that the V3/glycans should remain a high-priority vaccine candidate. Since targeting the V3/glycans was associated with breadth and potency in this cohort, the study continued to look at this epitope to investigate the role of these glycans in neutralisation resistance of Tier 2 viruses. The HIV-1 Env is surrounded by glycans that often prevent antibody neutralisation, leading to the term the "glycan shield", however some bnAbs have evolved to recognise these carbohydrates. Chapter 4 of this thesis describes how the N-linked glycan at position N301 is critical for maintaining neutralisation resistance of one subtype C virus (Du156.12), but not for another subtype-matched virus (CAP45.2.00.G3). Thus, the loss of the N301 glycan may have a substantial antibody-related fitness cost for some viruses but not others. The N301 glycan, as well as glycans at positions 332 and 334, are the primary targets of the anti-V3/glycan class of neutralising antibodies, which may select for loss of the targeted glycan. The evidence presented in Chapter 4 suggests that in some viruses, loss of the N301 glycan may result in evasion of anti-V3/glycan antibody responses while maintaining overall neutralisation resistance. This phenomenon may impair efficacy of passively-infused anti-V3/glycan bnAbs or a therapeutic vaccine.